The Role of Muay Thai Training in Improving Physical Fitness and VO₂max in Sedentary Adults: A Narrative Review - Al Husni Hadi Pasca Putra; Julia Windi Gunadi; Yenni Limyati; Oeij Anindita Adhika (Universitas Malahayati, 2026)
Aging is a physiological process that results in a gradual decline in physical fitness. Sedentary lifestyles are spreading throughout the world due to a limited availability of spaces for physical activity, coupled with more sedentary lifestyles resulting from office-based jobs and the widespread use of televisions and video devices, which has led to an increase in inactivity and numerous harmful effects on health. Exercise with various modalities can maintain several components of physical fitness, thereby slowing or mitigating the negative effects of aging on physical fitness. Muay Thai is a famous martial arts sport from Thailand. A martial arts-based physical training program with